NEGOTIATING IDENTITY AND AUTONOMY: THE INTERSECTION OF RELIGION, CULTURE, AND SOCIAL NETWORKS IN THE POLITICAL PREFERENCES OF MUSLIM WOMEN IN NORTH SUMATRA - Raihani Dewi Nasution Nasution; Katimin Katimin; Junaidi Junaidi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study analyzes the formation of political preferences among Muslim women in North Sumatra during the 2024 General Election, focusing on the dynamic intersection of religion, culture, and social networks. Drawing on data from 152 respondents collected through online surveys and in-depth interviews, the study finds that culture, particularly through family norms, domestic responsibilities, and spousal influence, emerges as the most dominant factor (93.4%) in shaping electoral decisions. Religion (77.6%) functions as a source of moral legitimation but is often actualized within cultural contexts and channeled through social networks. Social networks (42.1%) act as conduits for political narratives, primarily via social media and religious figures. This research challenges the simple dichotomy between agency and structure, demonstrating that women’s political autonomy does not always equate to individual independence but often manifests as a form of reflective obedience—wherein choices are forged through a negotiation between religious values, familial demands, and personal aspirations. These findings indicate that women are not merely passive recipients of influence but actively interpret and assign meaning to their political choices. To enhance women’s substantive participation, empowerment strategies must be holistic, addressing the transformation of family norms, the reinforcement of an inclusive religious identity, and the strengthening of social capacity. Consequently, the domestic sphere can be transformed from a restrictive space into a political power base for Muslim women.